2012
DOI: 10.4149/gpb_2012_015
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional characteristics of models of experimental myocardial injury induced by isoproterenol

Abstract: Abstract. The animal models of myocardial injury induced by systemic β-adrenergic receptor agonist administration represent an experimental approach of persisting interest. These models were found useful especially for studies of structural and functional adaptation of myocardium during the progression of cardiac adaptive response towards maladaptive hypertrophy and insufficiency. The pathological alterations induced by isoproterenol (ISO) do not develop evenly. The ISO models may contribute effectively to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 66 publications
4
95
0
2
Order By: Relevance
“…Isoproterenol-induced β-adrenergic overload leads to cardiac cell dysfunction, which is a good example of chemically-induced heart toxicity and failure (Nichtova et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Isoproterenol-induced β-adrenergic overload leads to cardiac cell dysfunction, which is a good example of chemically-induced heart toxicity and failure (Nichtova et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…15 Thus isoproterenol (ISO), the agonist of β-AR, has been widely used to establish the animal model of cardiac hypertrophy. 16,17 ISO is reported to induce both chronic and acute cardiac hypertrophy in animal experiments. The chronic cardiac hypertrophy model is used to simulate the chronic progression of heart remodeling in some chronic cardiovascular diseases such as hypertension.…”
mentioning
confidence: 99%
“…Consistent with other studies under the conditions of our assays,26 we find that low doses of AngII infusion in WT mice induced significant cardiac hypertrophy without causing significant cardiac systolic failure. Isoproterenol acts on β‐adrenergic receptors, resulting in increased heart rate and cardiac overload 25, 26. Consequently, increased myocardium oxygen demand and stress results in cardiac remodeling accompanied by myocardial necrosis, hypertrophy, and fibrosis 25, 44.…”
Section: Discussionmentioning
confidence: 99%
“…Isoproterenol acts on β‐adrenergic receptors, resulting in increased heart rate and cardiac overload 25, 26. Consequently, increased myocardium oxygen demand and stress results in cardiac remodeling accompanied by myocardial necrosis, hypertrophy, and fibrosis 25, 44. In this study, we found that a moderate‐dose isoproterenol treatment resulted in LV systolic dysfunction and fibrosis without inducing cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation